The Effect of Information Search Method on the Ability to Write Fable Story Texts of Students in Class VII of SMP Muhammadiyah 8 Medan in Learning Year 2019/2020 - Rahmadani, Dwi Ananda; H, Hasnidar (Journal of Innovation in Research, Education and Culture (JIREC), 2024)
This research aims to determine the ability to write fable text using the information search method and lecture method by Class VII Students of SMP Muhammadiyah 8 Medan in the 2019/2020 Academic Year and to determine the effect of the information search method on the ability to write fable text by Class VII Students of SMP Muhammadiyah 8 Medan 2019-2020 Learning Year. The method used in this research is the experimental method. This method was used because the researcher wanted to know the effect of the information search method on the ability to write fable text by Class VII Students of SMP Muhammadiyah 8 Medan in the 2019-2020 Academic Year. The sample used in this research was VII B with 28 students as the experimental class and class VII A as many as 29 students as the control class. From the research results, it can be concluded that the average writing ability of Class VII students at SMP Muhammadiyah 8 Medan in the 2019/2020 academic year using the information search method is 71.5 . The average writing ability of Class VII students of SMP Muhammadiyah 8 Medan in the 2019/2020 academic year using the lecture method is 55.8 . The writing ability of Class VII students of SMP Muhammadiyah 8 Medan for the 2019/2020 academic year using the information search method for the 2019/2020 academic year was at 57.12 % with a total of 16 students. The writing ability of Class VII students of SMP Muhammadiyah 8 Medan in the 2019/2020 academic year using the lecture method was at 48.27 % with a total of 14 students. Based on the t test by comparing the values of tcount with ttable, it is obtained that tcount > ttable or 3.06 > 2.004, so that Ha is accepted and Ho is rejected, meaning that there is a significant influence on writing fable text using the Information search method. Keywords: Influence, Information Search Method, Fable Story Text